(untitled) (Fiep Bulletin - online, 2015)
With the change of the rules of the Futsal game in last the 10 years the Maximum Force, Force Resistance and Explosive Force had become determinated capacities in an athlete income.This way , a training resisted program Â in the water was elaborated (Water Force) and it was applied in the volunteers to inquire it effect. The sample was composed by Professional Futsal players of the Santista selection who was: age 23 years, height 1,77m and 71,490 weight kg. It was used as comparative parameters: battery of testsfor maximum force, resistance Resistance and Explosive Force, cited for Giannichi(1998).The training had occurred 3 times a week for 50 minutes for each session, the athletes did 3 series of 10 to15 repetitions for each muscular group respecting the interval of 45 seconds between each series. After 12 weeks of training all the group was reevaluated in order toobserve the training results The results had demonstrated positive alterations in all the strength variations, demonstrating efficiency of the considered program.